Aristotle’s human virtue and Yorùbá worldview of ọmọlúàbí: an ethical-cultural interpretation (2016)
This paper gives an interpretative ethical-cultural analysis of the Aristotelian concepts of virtue in ancient Greece and Omoluabi in Yoruba worldview through the four Cardinal virtues of prudence, justice, courage and temperance. Generally, virtue and vices are common terminologies in ethical theories. They constitute significant principles or rules for moral actions. Virtues are ways of describing the habit of following those principles and rules. However, Aristotle, rather than explaining right or wrong in terms of rules, appraises the human characteristics through actions that make a person virtuous, enabling him to act ethically or acceptably under different circumstances that cannot be covered by rules or principle. Aristotle developed a significant description of human virtue in two of his texts, the Nicomachean Ethics and the Eudemian Ethics and reached several conclusions on what it means for a person to be virtuous. In the Nicomachean Ethics, Aristotle describes virtue as qualities needed to live morally and to achieve the overall purpose in life - happiness. He maintains that striking a balance between a deficiency and an excess of a trait is important. He considers virtue as a state of being which abets a person to live according to reason. Aristotle’s virtue relates to the Yoruba ideology of Omoluabi the philosophical and cultural concept used to describe someone of good and virtuous nature. An omoluabi is expected to display and exhibit great virtues and values translating the core moral conduct in Yoruba culture, such as humility, good-naturedness, bravery, good will, diligence among others